PREDICTION OF POROSITY DISTRIBUTION AT TALANG AKAR FORMATION IN JAMBI SUB-BASIN, USING SIMULTANEOUS INVERSION METHOD AND CLUSTER TRANSFORM - SISWANTO (NIM : 22309006), HADI
Talang Akar formation is one of the formations at South Sumatra basin that produce hydrocarbons. In general the lithology of Talang Akar formation is composed of sandstone, shalestone, and coal. Due to variation of reservoir thickness from varying porosity as well, so it needs a special strategy to separate the sand that has good porosity and poor porosity. In this case the simultaneous inversion, method, Extended Elastic Impedance (EEI) and clusters transform is used to separate porosity of sand. Based on a sensitivity test, the parameters in each well of the AI in croosplot with vshale show consistency for lithology differences. This causes the acoustic parameters and vshale can be applied in reservoir characterization. .In this case the simultaneous inversion method used to obtain P-impedance input for cluster transform to get a good-poor porosity, while the inversion EEI can be applied to obtain the distribution of shale volume, validation for distribution of good-poor porosity produced by the method of cluster transform. Not only for porosity clustering, cluster transform with validation of distribution of shale volume also assist in the interpretation of the sedimentation at Talang Akar formation. Horizon slice give an information about thickness and distribution patterns in the sand layer. Assisted by interpretation of seismic data and well data is known that the general direction of sedimentation is SW-WE and focusing of fine sand is at altitude areas in Southwest and Northeast.